Tipping the lysine methylation balance in disease1. Issue 2 (22nd November 2012) - Black, Joshua C.; Whetstine, Johnathan R.; Trievel, Ray
Abstract Genomic instability is a major contributing factor to the development and onset of diseases such as cancer. Emerging evidence has demonstrated that maintaining the proper balance of histone lysine methylation is critical to preserve genomic integrity. Genome‐wide association studies, gene sequencing, and genome‐wide mapping approaches have helped identify mutations, copy number changes, and aberrant gene regulation of lysine methyltransferases (KMTs) and demethylases (KDMs) associated with cancer and cognitive disorders. Structural analysis of KMTs and KDMs has demonstrated the drugability of these enzymes and has led to the discovery of small molecule inhibitors. Use of these inhibitors has allowed better understanding of the biochemical properties of KMTs and KDMs and demonstrated potential for therapeutic use. This review will highlight the methyl modifications, KMTs and KDMs associated with cancer and neurological disorders and how KMT and KDM and the potential for treatment of these conditions with small molecule inhibitors. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 127–135, 2013.